2018
DOI: 10.3847/1538-4357/aaa42a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reconnaissance of the β Pictoris Gas Disk with the SMA: A Low HCN/(CO+CO2) Outgassing Ratio and Predictions for Future Surveys

Abstract: The exocometary origin of CO gas has been confirmed in several extrasolar Kuiper belts, with CO ice abundances consistent with Solar System comets. We here present a molecular survey of the β Pictoris belt with the Submillimeter Array (SMA), reporting upper limits for CN, HCN, HCO + , N 2 H + and H 2 CO, as well as for H 2 S, CH 3 OH, SiO and DCN from archival ALMA data. Non-detections can be attributed to rapid molecular photodissociation due to the Astar's strong UV flux. CN is the longest-lasting and most e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 54 publications
2
80
0
Order By: Relevance
“…rich planetesimals, and so that all have associated secondary gas disks, but that only a fraction of these have CO at detectable levels. While no other gas molecules have been detected in debris disks, this is to be expected given the lower abundance relative to CO and moreover the even shorter lifetime of most molecules (Matrà et al 2018b).…”
Section: Planetesimal Compositionmentioning
confidence: 94%
“…rich planetesimals, and so that all have associated secondary gas disks, but that only a fraction of these have CO at detectable levels. While no other gas molecules have been detected in debris disks, this is to be expected given the lower abundance relative to CO and moreover the even shorter lifetime of most molecules (Matrà et al 2018b).…”
Section: Planetesimal Compositionmentioning
confidence: 94%
“…Fig. 2a, except for β Pic where it was taken from Matrà et al (2018a). As the plot shows, while the CO content of β Pic can be explained within an unshielded or weakly shielded model, all CO-rich disks require substantial shielding with CO > 100, i.e.…”
Section: Shielding Of Co Gas In 49 Cet and Hd 32297mentioning
confidence: 96%
“…Matrà et al (2017a,b) and Marino et al (2016) found that the CO+CO 2 mass abundances of the comets in the β Pic, Fomalhaut and HD 181327 disks are consistent with abundances measured in solar system comets. Using data from the Submillimeter Array (SMA), Matrà et al (2018) showed that the comets in the β Pic disk have a HCN/(CO+CO 2 ) ratio of outgassing rates that is consistent with, but at the low end of, what is observed for solar system comets. This might be caused by the outgassing mechanism, or it might indicate a true depletion of HCN with respect to solar system comets.…”
Section: Introductionmentioning
confidence: 77%